2012
DOI: 10.2190/ns.22.3.b
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Take Action: The Goals of Health and Safety Training

Abstract: Worker health and safety training is an important part of occupational health and safety programs. In the United States, governments, unions, employers, university programs, and health and safety advocacy organizations make training available. This article considers training effectiveness research conducted and supported by the National Institute for Occupational Safety and Health (NIOSH), and some done in collaboration with the Institute for Work and Health (Canada). Differing perspectives regarding the purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
(34 reference statements)
0
20
0
3
Order By: Relevance
“…Structural change is slow. Workers need the tools to recognize and minimize, if not overcome, barriers while simultaneously empowering them to advocate for removal of these barriers [Weinstock and Slatin, 2012]. Identifying structural barriers, understanding the daily consequences for and coping strategies of workers, and developing interventions to increase the ability of workers to minimize, if not eliminate, these barriers would be a direction for future training intervention research.…”
Section: Discussionmentioning
confidence: 99%
“…Structural change is slow. Workers need the tools to recognize and minimize, if not overcome, barriers while simultaneously empowering them to advocate for removal of these barriers [Weinstock and Slatin, 2012]. Identifying structural barriers, understanding the daily consequences for and coping strategies of workers, and developing interventions to increase the ability of workers to minimize, if not eliminate, these barriers would be a direction for future training intervention research.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars writing in the American Journal of Public Health concluded that “[a]s training methods became more engaging (i.e., requiring trainees' active participation), workers demonstrated greater knowledge acquisition, and reductions were seen in accidents, illnesses, and injuries” [9]. Weinstock and Slatin in a New Solutions issue devoted to health and safety training discuss the importance of “helping workers establish the power to reduce and eliminate workplace hazards” [10] as a key training goal. They go on to review the literature of empowerment-oriented health and safety training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Almost no respondents prioritized active involvement in H&S programs or emergency response activities as most important in their expectations of training. An appreciation of training as a means to encourage employee engagement in workplace H&S programs could further enhance the value of training by giving trained employees opportunities to provide input into site-specific H&S program components [Cohen & Colligan, 1998; Becker & Morawetz, 2004; Weinstock & Slatin, 2012]. Future H&S training research should further investigate factors supporting or discouraging managers’ decisions to involve trained workers in aspects of their H&S programs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have generated important lessons about effective training methods, including the value of hands-on approaches that provide opportunities for interaction and dialogue [Burke et al, 2006] and that engage workers in activities to identify, control, and prevent hazards in their work environment [Weinstock and Slatin, 2012]. Few studies to date, however, have considered this training from the management point of view—their reasons for providing training, or their perception of whether training contributes to preventing hazardous incidents and exposures.…”
Section: Introductionmentioning
confidence: 99%